Feasibility evaluation method and application of moderate in-situ gasification in deep tight coal & gas reservoirs - KANG Yili, SHAO Junhua, LIU Jiarong, CHEN Mingjun, YOU Lijun, CHEN Xueni, CAO Wangkun (Youqicang pingjia yu kaifa)
In order to establish a systematic evaluation of deep tight coal reservoirs and ensure the efficient, economic and safe implementation of moderate in-situ gasification projects in deep tight coal reservoirs, a feasibility evaluation method based on fuzzy analytic hierarchy process was developed. The methodology comprises: (1) the establishment of an evaluation index set of 3 first-level indicators, including resource conditions, reservoir conditions and preservation conditions, and 18 second-level indicators, including parameters such as coal rank, coal rock reservoir thickness, and coal rock reservoir pressure coefficient, along with a graded comment set categorizing outcomes as “feasible”, “basically feasible”, and “infeasible”; (2) the determination of indicator weights through the analytic hierarchy process; (3) the calculation of each indicator’s membership degree using a trapezoidal membership function to construct an evaluation matrix; and (4) the synthesis of the evaluation and weight matrices to ascertain the membership degrees corresponding to “feasible”, “basically feasible”, and “infeasible” for candidate areas, thus determining the feasibility based on the principle of maximum membership degree. The evaluation method was applied to the feasibility evaluation of moderate in-situ gasification for the deep No. 8 tight coal reservoir in the M block of the Ordos Basin. The evaluation results show that the membership degrees of “feasible”, “basically feasible” and “infeasible” for moderate in-situ gasification of No. 8 coal reservoir in the deep part of M block are 0.413, 0.425 and 0.162 respectively, with the maximum being 0.425, thus determining the feasibility as “basically feasible”. The comprehensive quantitative feasibility evaluation method of moderate in-situ gasification of deep tight coal reservoir, which places particular emphasis on the evaluation of preservation conditions, provides scientific guidance for the implementation of moderate in-situ gasification projects in deep tight coal reservoirs.